(3GdJcQGQs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3bO SHb dfG bHd cJGHfG gPG KdGKI hNeShf cJGHoG ai LejY Gdafhf , hgPG GdcJGH CQHY hNeShf s
(3BNQgG (B:s
(3agPg GdYdGeGJ GdKdGK jfHZj eYQaJgG dJYed YdjgG s
(3Vef eLehY , JQJjHgG (B: 54s
(3hQOJ cPdc ai Qbe (B96 (3hgh GdebGdI GdQGHYI hGdNeShf ef cJGH GdSHYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B108 s
Keywords: (3GdcjejGA h GdWHjYjGJs